Antibody Responses to Phlebotomus papatasi Saliva in American Soldiers With Cutaneous Leishmaniasis Versus Controls - Aronson, Naomi E.; Oliveira, Fabiano; Gomes, Regis; Porter, William D.; Howard, Robin S.; Kamhawi, Shaden; Valenzuela, Jesus G. (Frontiers in Tropical Diseases, 2022)
Leishmania major, transmitted in Iraq by the bite of a sand fly Phlebotomus papatasi causes cutaneous leishmaniasis (CL). The sand fly saliva is immunogenic, with both systemic humoral and cellular human immune responses resulting from natural exposure. 248 Americans who developed L. major infection in Iraq were gender, race/ethnicity, year of Iraq deployment-matched to controls without CL. Using a case-control study design, we compared sand fly saliva-specific human IgG levels and proteins between the two groups. Serologic responses to Ph. papatasi salivary gland homogenate were studied with ELISA and Western blot, using serial samples obtained from before travel, during CL treatment (CL) or at time to return to US (controls), as well as (for CL cases) six to 24 months after return to non-endemic US. The mean change in optical density (MCOD), reflecting the change in sand fly saliva-specific IgG before and after exposure in Iraq, was 0.296 (range -0.138-2.057) in cases and 0.151 (range -0.454-1.085) in controls, p<0.001. Low levels of sand fly saliva specific IgG were noted in CL cases by 7-8 months after return to the US. The most frequently recognized serologic responses were to MW30 (PpSP32) and MW64 Ph. papatasi salivary proteins, although other salivary proteins recognized were MW12/14,15,18,28,32,36,42,44,46,52. Logistic regression suggested that MW15, 28 and 42 had the largest effect on the MCOD. MW30 was the most frequent response suggesting a role as biomarker for sand fly exposure and CL. Antibody waned within months of return to the US. We also present vector saliva immune responses in the context of CL presentation and identify some salivary protein bands that may correlate with less lesion area, ulcer versus papule/plaque, race among those with CL.